THE ROLE OF ENVIRONMENTAL MARKETING AWARENESS IN ENHANCING CUSTOMER CITIZENSHIP BEHAVIOR: "An analytical study of the opinions of a sample of individuals working in industrial organizations in the city of dohuk" - Omar, Mohammed (Humanities Journal of University of Zakho, 2024)
The paper aims at providing a clear concept of environmental marketing awareness and its role in enhancing customer citizenship behavior for industrial organizations in the city of Dohuk, benefiting from the creative capabilities of workers and modern technologies that the organizations understudy possess on an ongoing basis. Environmental marketing stems from the interest in the customer as the basic pillar in the markets. This enables organizations to outperform competing organizations. The current paper has relied on testing environmental marketing awareness as an independent variable with its factors and customer citizenship behavior as a dependent variable with its dimensions. An analytical analysis is used in order to identify the nature of relationship of correlation and influence between the independent and dependent variables. A number of main and sub-hypotheses were formulated and tested through the use of a set of analytical statistical methods. A number of 74 valid forms were retrieved for statistical analysis. The findings concluded that the industrial organizations need to look for advanced strategies to generate economic value, allowing to create a vision for it through the perspective of responsibility in protecting the environment and preserving its resources in a sustainable manner. Finally, it is recommended that the industrial organizations need to develop, produce and provide environmentally friendly products that are efficient and effective in contributing to reduce environmental pollution processes.